The Genetic Predisposition to Obesity Has No Influence on Waist Circumference When Screen Time and Sleep Duration Are Adequate in Children and Adolescents - Garcia-Hermoso, A (Taylor and Francis Ltd., 2022)
The aim of the present study was to verify whether the amount of sleep duration, screen time, and physical activity moderate the relationship between FTO rs9939609 polymorphism and waist circumference (WC) in children and adolescents. This is a cross-sectional study conducted with 1338 children and adolescents, aged between 6 and 17 years. Lifestyle habits were assessed through self-reported questionnaire. WC was measured on the narrowest part of the trunk between the last rib and the iliac crest. FTO rs9939609 polymorphism was genotyped by real time polymerase chain reaction. The PROCESS macro for the SPSS was used for moderation analyses, through multiple linear regression models. Results indicated significant interactions were found between sleep duration and screen time X FTO rs9939609, showing that these lifestyle behaviours are moderators in the relationship between a genetic predisposition for obesity and higher WC. For physical activity, there was no significant interaction. Therefore, sleeping more than 564 min a day (i.e. 9.4 h) and spending no more than 233 min in front of screen may counteract the genetic predisposition to obesity in children and adolescents. Highlights A healthy lifestyle may counteract the genetic predisposition to central obesity; Children and adolescents should sleep more than approximately 9 h (564 min) per day and spend less than approximately 4 h (233 min) per day in front of screens in order to counteract the genetic predisposition to central obesity conferred by the FTO gene variant. It is fundamental to promote actions for the adoption of a healthy lifestyle, including the importance of presenting adequate sleep habits and low screen time for a better cardiometabolic health and reduction of obesity. © 2021 European College of Sport Science.